Polymer, preparation method and application thereof, and modifying and flooding agent
By designing a polymer containing cyclodextrin structural unit, the existing polymers have been solved inadequate performance under high temperature and high salinity conditions, and the temperature resistance, salt resistance and adsorption resistance of polymers in oil fields have been improved. , and exhibit excellent results in oil-fighting and oil-fouling washing in oil fields.
Patent Information
- Application Number
- CN202310789317.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2043-06-30
AI Technical Summary
The existing polymers exhibit poor temperature, salt and adsorption resistance under high temperature and high salinity conditions, which limits their promotion and application in oil fields.
A polymer was designed that contains specific structural units A, B and C, and cyclodextrin is introduced through covalent bonding to form a polymer with a rigid structure, improving its temperature, salt and adsorption resistance, and adopting As a raw material, cyclodextrin maleate esterides can achieve efficient preparation of polymers through specific polymerization conditions and combinations of initiators.
The viscosity retention rate of polymer at 85°C is ≥90%, the viscosity retention rate of polymer at 100,000 mg/L mineralization degree is ≥80%, the static adsorption viscosity retention rate is ≥85%, and it has excellent oil displacement effect and washing performance, suitable for Oilfield oil-repellent and oil-fouling detergent.
Smart Images

Figure CN119219846A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of chemical oil displacement agents, and in particular to a polymer, a preparation method and application thereof, and a displacement agent. Background Art
[0002] Polymer flooding is currently one of the important means to improve oil recovery in oil fields. Although partially hydrolyzed polyacrylamide (HPAM) exhibits excellent thickening, viscoelastic and rheological properties, its viscosity decreases sharply with increasing temperature and salinity. In practical applications, it is necessary to increase the concentration of HPAM, which will lead to a sharp increase in production costs, and then limit its promotion and application in high-temperature and high-salinity reservoirs. Therefore, the development of temperature-resistant and salt-resistant polymers is crucial to improving oil recovery.
[0003] "Improved viscoelasticity of xanthan gum through self-association with surfactant: β-cyclodextrin inclusion complexes for applications in enhanced oil recovery" (L Romero-Zerón, Rodrigue D. Polymer Engineering & Science, 2015, 55(3): 523-532.) Cyclodextrin is mixed with xanthan gum and an ionic surfactant to form a self-assembled system with a host-guest network structure for improving oil recovery. However, only weak interactions exist in the above system, and there is a problem of poor anti-adsorption performance.
[0004] Based on this, there is an urgent need to provide a supramolecular polymer with temperature resistance, salt resistance and adsorption resistance. Summary of the invention
[0005] The purpose of the present invention is to overcome the problems of poor temperature resistance, salt resistance and anti-adsorption performance of polymers in the prior art, and to provide a polymer and its preparation method and application as well as a displacement agent, wherein the polymer has strong salt resistance, temperature resistance and anti-adsorption performance.
[0006] In order to achieve the above object, the first aspect of the present invention provides a polymer, wherein the polymer comprises at least one structural unit A represented by formula (1), at least one structural unit B represented by formula (2) and at least one structural unit C represented by formula (3), wherein:
[0007]
[0008] Among them, R 1 H, C 1 -C18 Alkyl, -R 2 -SO 3 H, -R 3 -COOH or Among them, R 2 C 3 -C 4 A straight chain or branched alkyl group, R 3 C 4 -C 8 A straight chain or branched alkyl group, n is an integer of 0-2, R 4 H or C 1 -C 4 The straight chain alkyl group, R 5 is H or methyl;
[0009] Y is selected from the structure shown in Formula I, the structure shown in Formula II, the structure shown in Formula III or the structure shown in Formula IV,
[0010]
[0011]
[0012] Wherein, a is an integer from 0 to 22, b is 2, c is 1, d is 2 or 3, R 6 is -COO- or -CO-NH-, and X is each independently halogen;
[0013] Z is the residue after dehydroxylation of cyclodextrin.
[0014] The second aspect of the present invention provides a method for preparing a polymer, wherein the method comprises: mixing at least one monomer A represented by formula (4), at least one monomer B represented by formula (5) and at least one monomer C represented by formula (6) with water to obtain a monomer mixed solution, adjusting the pH value of the monomer mixed solution, adding an initiator, performing a polymerization reaction under a nitrogen atmosphere, and obtaining a polymer through post-treatment;
[0015]
[0016] Among them, R 1 ' is H, C 1 -C 18 Alkyl, -R 2 '-SO 3 H, -R 3 '-COOH or Among them, R 2 ' is C 3 -C 4 A straight chain or branched alkyl group, R 3 ' is C 4 -C 8A straight chain or branched alkyl group, n' is an integer from 0 to 2, R 4 ' is H or C 1 -C 4 The straight chain alkyl group, R 5 ' is H or methyl;
[0017] Y' is selected from the structure shown in formula I', the structure shown in formula II', the structure shown in formula III' or the structure shown in formula IV',
[0018]
[0019]
[0020] Wherein, a' is an integer from 0 to 22, b' is 2, c' is 1, d' is 2 or 3, R 6 ' is -COO- or -CO-NH-, X' is each independently a halogen;
[0021] Z' is the residue after dehydroxylation of cyclodextrin.
[0022] The third aspect of the present invention provides a polymer obtained by the above preparation method.
[0023] A fourth aspect of the present invention provides a use of the above polymer as a displacement agent.
[0024] A fifth aspect of the present invention provides a use of the above polymer as an oil stain detergent.
[0025] A sixth aspect of the present invention provides a displacement agent, wherein the displacement agent comprises the above-mentioned polymer and water.
[0026] Through the above technical solution, a polymer, a preparation method and application thereof, and a displacement agent provided by the present invention have the following beneficial effects:
[0027] The polymer of the present invention comprises a structural unit A represented by formula (1), a structural unit B represented by formula (2) and a structural unit C represented by formula (3), so that the polymer has excellent heat resistance, salt resistance and adsorption resistance. Specifically, through the structural unit C, a cyclodextrin having a rigid structure is introduced into the polymer through a covalent bond, so that the polymer has obvious heat resistance, salt resistance and shear resistance. At 85°C, the viscosity retention rate of the polymer is ≥90%, and the polymer has the characteristics of high temperature resistance, and the temperature resistance reaches above 85°C. At a mineralization of 100,000 mg / L, the viscosity retention rate of the polymer is ≥80%, and the polymer has high salt resistance, and the salt resistance can reach a mineralization of more than 100,000 mg / L. The structural unit B represented by formula (2) is introduced to make the polymer have excellent adsorption resistance, and the static adsorption viscosity retention rate of the polymer is ≥85%.
[0028] The polymer prepared by using the monomers shown in formulas (4) to (6) as raw materials in the polymer preparation process provided by the present invention has excellent heat resistance, salt resistance and anti-adsorption properties; and the maleic acid cyclodextrin ester is used as the raw material, which is environmentally friendly. At the same time, the synthesis conditions of the polymer are easy to control, the reaction process is stable, and it is easier to realize industrialization.
[0029] The displacement agent made of the polymer of the present invention has an excellent oil displacement effect, and its static oil removal rate is ≥90%. The polymer of the present invention is applied to the oil stain detergent. Since the cyclodextrin structure with internal hydrophilicity and external hydrophobicity is introduced into the polymer, it has the properties of a surfactant, so it can play a washing role without phase separation, and the oil stain cleaning rate reaches more than 80%. DETAILED DESCRIPTION
[0030] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0031] The first aspect of the present invention provides a polymer, wherein the polymer comprises at least one structural unit A represented by formula (1), at least one structural unit B represented by formula (2) and at least one structural unit C represented by formula (3), wherein:
[0032]
[0033] Among them, R 1 H, C 1 -C 18 Alkyl, -R 2 -SO 3 H, -R 3 -COOH or Among them, R 2 C 3 -C 4 A straight chain or branched alkyl group, R 3 C 4 -C 8 A straight chain or branched alkyl group, n is an integer of 0-2, R 4 H or C 1 -C 4 The straight chain alkyl group, R 5 is H or methyl;
[0034] Y is selected from the structure shown in Formula I, the structure shown in Formula II, the structure shown in Formula III or the structure shown in Formula IV,
[0035]
[0036] Wherein, a is an integer from 0 to 22, b is 2, c is 1, d is 2 or 3, R 6 is -COO- or -CO-NH-, and X is each independently halogen;
[0037] Z is the residue after dehydroxylation of cyclodextrin.
[0038] In the present invention, the polymer comprises a structural unit A represented by formula (1), a structural unit B represented by formula (2) and a structural unit C represented by formula (3), so that the polymer has excellent heat resistance, salt resistance and adsorption resistance. Specifically, through the structural unit C, a cyclodextrin having a rigid structure is introduced into the polymer through a covalent bond, so that the polymer has obvious heat resistance, salt resistance and shear resistance. At 85°C, the viscosity retention rate of the polymer is ≥90%, and the polymer has the characteristics of high temperature resistance, and the temperature resistance reaches above 85°C. At a mineralization of 100,000 mg / L, the viscosity retention rate of the polymer is ≥80%, and the polymer has high salt resistance, and the salt resistance can reach a mineralization of more than 100,000 mg / L. The structural unit B represented by formula (2) is introduced to make the polymer have excellent adsorption resistance, and the static adsorption viscosity retention rate of the polymer is ≥85%.
[0039] In the present invention, the R 6 The carbon atom in formula (2) is connected to the carbon atom in formula (2).
[0040] Furthermore, R 1 H, C 3 -C 12 Alkyl, -R 2 -SO 3 H, -R 3 -COOH or Among them, R 2 is isobutyl; R 3 isobutyl, n is 0 or 1, R 4 H or C 1 -C 2 The alkyl group, R 5 For H.
[0041] Furthermore, a is an integer of 0-18, b is 2, c is 1, d is 2 or 3, R 6 is -COO- or -CO-NH-, and X is a chloride ion.
[0042] Furthermore, the cyclodextrin is selected from at least one of α-cyclodextrin, β-cyclodextrin, γ-cyclodextrin, 2-hydroxypropyl-β-cyclodextrin and 2-hydroxypropyl-γ-cyclodextrin.
[0043] According to the present invention, based on the total mass of the polymer, the content of the structural unit A is 40-65wt%, the content of the structural unit B is 5-30wt%, and the content of the structural unit C is 15-40wt%.
[0044] In the present invention, when the contents of the structural unit A, the structural unit B and the structural unit C in the copolymer meet the above-mentioned definitions, the polymer has better temperature resistance, salt resistance and anti-adsorption properties.
[0045] In the present invention, the sum of the contents of the structural unit A, the structural unit B and the structural unit C is 100 wt %.
[0046] Furthermore, based on the total mass of the polymer, the content of the structural unit A is 45-63wt%, the content of the structural unit B is 7-29wt%, and the content of the structural unit C is 18-35wt%.
[0047] According to the present invention, the structural unit B includes the structure shown in formula (2-1) and the structure shown in formula (2-2);
[0048]
[0049] In the present invention, when the structure represented by formula (2-1) and the structure represented by formula (2-2) are simultaneously used as structural unit B, a synergistic effect can be produced between the two structures, thereby further improving the temperature resistance, salt resistance and anti-adsorption properties of the polymer.
[0050] According to the present invention, in the structural unit B, the weight ratio of the structure represented by the formula (2-1) to the structure represented by the formula (2-2) is 1-4:1.
[0051] Furthermore, in the structural unit B, the weight ratio of the structure represented by the formula (2-1) to the structure represented by the formula (2-2) is 1-3.5:1.
[0052] According to the present invention, the viscosity-average relative molecular weight of the polymer is 1,000,000-8,000,000 g / mol.
[0053] Furthermore, the viscosity-average relative molecular weight of the polymer is 1,000,000-6,000,000 g / mol.
[0054] The second aspect of the present invention provides a method for preparing a polymer, wherein the method comprises: mixing at least one monomer A represented by formula (4), at least one monomer B represented by formula (5) and at least one monomer C represented by formula (6) with water to obtain a monomer mixed solution, adjusting the pH value of the monomer mixed solution, adding an initiator, performing a polymerization reaction under a nitrogen atmosphere, and obtaining a polymer through post-treatment;
[0055]
[0056] Among them, R 1 ' is H, C 1 -C 18 Alkyl, -R 2 '-SO 3 H, -R 3 '-COOH or Among them, R 2 ' is C 3 -C 4 A straight chain or branched alkyl group, R 3 ' is C 4 -C 8 A straight chain or branched alkyl group, n' is an integer from 0 to 2, R 4 ' is H or C 1 -C 4 The straight chain alkyl group, R 5 ' is H or methyl;
[0057] Y' is selected from the structure shown in formula I', the structure shown in formula II', the structure shown in formula III' or the structure shown in formula IV',
[0058]
[0059]
[0060] Wherein, a' is an integer from 0 to 22, b' is 2, c' is 1, d' is 2 or 3, R 6 ' is -COO- or -CO-NH-, X' is each independently a halogen;
[0061] Z' is the residue after dehydroxylation of cyclodextrin.
[0062] In the present invention, the polymer prepared by using the monomers represented by formulas (4) to (6) as raw materials in the polymer preparation process has excellent heat resistance, salt resistance and anti-adsorption properties; and maleic acid cyclodextrin ester is used as the raw material, which is environmentally friendly. At the same time, the synthesis conditions of the polymer are easy to control, the reaction process is stable, and it is easier to realize industrialization.
[0063] In the present invention, the maleic acid-cyclodextrin ester can be prepared according to the prior art method. Preferably, the preparation method of the maleic acid-cyclodextrin ester comprises: weighing cyclodextrin (α-cyclodextrin, β-cyclodextrin, γ-cyclodextrin, 2-hydroxypropyl-β-cyclodextrin or 2-hydroxypropyl-γ-cyclodextrin) and maleic anhydride according to a mass ratio of 1:0.5-1.5, stirring and mixing with N,N-dimethylformamide, and heating the mixture solution at 70-90°C for 8-12 hours. After the reaction is completed, the solution is cooled and chloroform is added, and then washed with acetone and dried.
[0064] In the present invention, the R 6 The carbon atom in ' is connected to the carbon atom in formula (6).
[0065] Furthermore, R 1 ' is H, C 3 -C 12 Alkyl, -R 2 '-SO 3 H, -R 3 '-COOH or Among them, R 2 ' is isobutyl; R 3 ' is isobutyl, n' is 0 or 1, R 4 ' is H or C 1 -C 2 The alkyl group, R 5 'For H.
[0066] Furthermore, a' is an integer of 0-18, b' is 2, c' is 1, d' is 2 or 3, R 6 ' is -COO- or -CO-NH-, and X' is a chloride ion.
[0067] Furthermore, the cyclodextrin is selected from at least one of α-cyclodextrin, β-cyclodextrin, γ-cyclodextrin, 2-hydroxypropyl-β-cyclodextrin and 2-hydroxypropyl-γ-cyclodextrin.
[0068] According to the present invention, based on the total weight of the monomer A, monomer B and monomer C, the amount of the monomer A is 40-65wt%, the amount of the monomer B is 5-30wt%, and the amount of the monomer C is 15-40wt%.
[0069] In the present invention, when the usage of monomer A, monomer B and monomer C is within the above range, the heat resistance, salt resistance and adsorption resistance of the polymer can be improved.
[0070] Furthermore, based on the total weight of the monomer A, the monomer B and the monomer C, the amount of the monomer A is 45-63wt%, the amount of the monomer B is 7-29wt%, and the amount of the monomer C is 18-35wt%.
[0071] According to the present invention, the monomer B includes the structure shown in formula (5-1) and the structure shown in formula (5-2);
[0072]
[0073] In the present invention, when the monomer B adopts the above combination, the obtained polymer has high temperature resistance, high salt resistance and high anti-adsorption performance.
[0074] According to the present invention, relative to the total amount of monomer B used, the amount ratio of monomer B with the structure represented by formula (5-1) to monomer B with the structure represented by formula (5-2) is 1-4:1.
[0075] According to the present invention, the initiator is selected from at least one of sodium bisulfite, sodium thiosulfate, sodium pyrosulfite, potassium persulfate, sodium persulfate, hydrogen peroxide, 2,2'-azo[2-(2-imidazolin-2-yl)propane]dihydrochloride, azobis(2,5-dimethyl-6-carboxy)hexanenitrile and 4,4'-azobis(4-cyanovaleric acid).
[0076] In the present invention, when the above initiator is selected, it is more conducive to the polymerization reaction between monomers, so that the polymer has the characteristics of less homopolymer content, and the obtained polymer has excellent temperature resistance, salt resistance and anti-adsorption properties.
[0077] Furthermore, the initiator is an initiator composition of potassium persulfate and sodium bisulfite, or an initiator composition of ammonium persulfate and sodium bisulfite.
[0078] In a preferred embodiment of the present invention, the sodium bisulfite is 20-35 parts by weight relative to 100 parts by weight of the initiator composition.
[0079] According to the present invention, based on the total weight of the monomer A, the monomer B and the monomer C, the added amount of the initiator is 0.1-0.6 wt %.
[0080] Furthermore, based on the total weight of the monomer A, the monomer B and the monomer C, the added amount of the initiator is 0.3-0.6 wt %.
[0081] According to the present invention, the pH value of the monomer mixed solution is adjusted to 6-8.
[0082] In the present invention, the monomer mixed solution is generally acidic, and those skilled in the art can use alkaline solution to adjust the pH of the monomer mixed solution according to actual conditions. Preferably, the alkaline solution can be a sodium hydroxide solution or a potassium hydroxide solution.
[0083] According to the present invention, the polymerization reaction temperature is 5-50° C., and the polymerization reaction time is 6-9 hours.
[0084] In the present invention, when the polymerization reaction meets the above conditions, it is more conducive to the polymerization between monomers and the reaction process is stable.
[0085] Furthermore, the polymerization reaction temperature is 10-40°C, and the polymerization reaction time is 7-8h.
[0086] In the present invention, the post-treatment includes: precipitation with an organic solvent, filtering, drying and crushing. The organic solvent can be selected from acetone, ethanol or methanol.
[0087] The third aspect of the present invention provides a polymer obtained by the above preparation method.
[0088] According to the present invention, the viscosity-average relative molecular weight of the polymer is 1,000,000-8,000,000 g / mol.
[0089] Furthermore, the viscosity-average relative molecular weight of the polymer is 1,000,000-6,000,000 g / mol.
[0090] A fourth aspect of the present invention provides a use of the above polymer as a displacement agent.
[0091] The polymer of the present invention has excellent heat resistance, salt resistance and adsorption resistance, can adapt to the environment of oil displacement operation, and the prepared displacement agent has excellent oil displacement effect, and its static oil removal rate is ≥90%, which can meet the oil displacement demand of the oil field.
[0092] A fifth aspect of the present invention provides a use of the above polymer as an oil stain detergent.
[0093] The polymer of the present invention is applied to oil stain detergents. Since the polymer is introduced with a cyclodextrin structure that is hydrophilic inside and hydrophobic outside, it has the properties of a surfactant and can therefore exert a washing effect without phase separation, and the oil stain cleaning rate reaches more than 80%.
[0094] In the present invention, water and polymer can be mixed according to actual needs to prepare an oil stain detergent. For example, the polymer is prepared into a 1-3wt% aqueous solution for use as an oil stain detergent, and the cleaning time can be 10-25 minutes.
[0095] A sixth aspect of the present invention provides a displacement agent, wherein the displacement agent comprises the above-mentioned polymer and water.
[0096] In the present invention, the displacement agent has excellent temperature resistance, salt resistance and adsorption resistance, can adapt to the environment of oil displacement operation, and the prepared displacement agent has excellent oil displacement effect, and its static oil removal rate is ≥90%.
[0097] According to the present invention, the polymer is present in an amount of 0.1-5 parts by weight, preferably 0.1-2.5 parts by weight, relative to 100 parts by weight of water.
[0098] According to the present invention, the displacement agent further comprises a surfactant.
[0099] In the present invention, the type and amount of the surfactant can be selected conventionally in the art, and the present invention is not limited thereto. For example, relative to 100 parts by weight of water, the surfactant is 0.1-10 parts by weight.
[0100] The present invention will be described in detail below through examples.
[0101] The content of each structural unit in the polymer is obtained by the raw material ratio estimation method.
[0102] The viscosity-average relative molecular weight of the polymer is measured by the calculation method of intrinsic viscosity and viscosity-average relative molecular mass in SY / T 5862-2020.
[0103] Oil removal rate: A static oil removal experiment at normal pressure was used for testing. Specifically: (1) Prepared oil sand: Quartz sand and crude oil were mixed at a mass ratio of 8:2, and then aged in an oven at a formation temperature of 45°C for 24 hours; (2) 15 g of oil sand was placed in a deoiling bottle, and after compaction, the polymer solution was injected to the 1 mL mark, and then placed in a constant temperature box. The volume of oil produced was recorded regularly, and the oil removal rate was calculated according to the volume of oil produced / the volume of crude oil × 100%.
[0104] Oil cleaning rate: the ratio of the mass of oil pollutants removed by cleaning to the total mass of oil pollutants on the test board; the cleaning is carried out by immersion, and the cleaning time is 15 minutes at 25°C.
[0105] The salt resistance of the polymer was evaluated by preparing a 0.01wt% aqueous solution of the polymer with clean water and 100000mg / L saline solution, respectively, and using a Brookfield viscometer, the apparent viscosity (in cP) of each solution was tested at 25°C and a speed of 6r / min. The viscosity retention rate in 100000mg / L saline solution is: the ratio of the apparent viscosity of the polymer in 100000mg / L saline solution to the apparent viscosity of the polymer in clean water × 100%.
[0106] The heat resistance of the polymer was evaluated by preparing a 0.01wt% aqueous solution of the polymer with clean water, and the apparent viscosity (in cP) of each solution was tested at 25°C, 45°C, 65°C and 85°C using a Brookfield viscometer at a speed of 6 r / min. The viscosity retention rate at 85°C was the ratio of the apparent viscosity of the polymer at 85°C to the apparent viscosity of the polymer at 25°C × 100%.
[0107] Evaluation of the anti-adsorption property of the polymer: The anti-adsorption property of the polymer of the present invention is evaluated by the static adsorption viscosity retention rate. The method comprises: (1) washing quartz sand with a particle size range of 30-40 mesh with deionized water and drying at 105°C, and repeating twice. The polymer is prepared with clean water to prepare a polymer aqueous solution with a mass concentration of 0.01wt%, and the apparent viscosity (in cP) of the polymer aqueous solution is tested at 75°C and a rotation speed of 6r / min using a Brookfield viscometer, and is recorded as η 0(2) Place 25 g of quartz sand in a 250 mL stoppered bottle, add 75 g of polymer aqueous solution, shake well and place in a constant temperature water bath oscillator, oscillate at a frequency of 120 times / min, and oscillate back and forth at 30°C for 24 h. Take out the sample, centrifuge it and take the upper clear liquid. Preheat the constant temperature water bath, and test the apparent viscosity of the solution again at 75°C and a speed of 6 r / min (in cP), recorded as η 1 The static adsorption viscosity retention rate is η 1 / η 0 ×100%.
[0108] Maleic anhydride, α-cyclodextrin, β-cyclodextrin, γ-cyclodextrin, 2-hydroxypropyl-β-cyclodextrin and 2-hydroxypropyl-γ-cyclodextrin raw materials are all commercially available products of Shanghai Aladdin Biochemical Technology Co., Ltd.
[0109] Initiator composition A: the mass ratio of ammonium persulfate to sodium bisulfite is 1:0.5;
[0110] Initiator composition B: the mass ratio of potassium persulfate to sodium bisulfite is 1:0.4;
[0111] Other raw materials used in the examples and comparative examples are all commercially available.
[0112] The room temperature described in the preparation examples is 25°C.
[0113] Preparation Example 1
[0114] Preparation of maleic acid-α-cyclodextrin ester: 9 g of α-cyclodextrin, 9 g of maleic anhydride and 8 mL of N,N-dimethylformamide were stirred and mixed, and the mixture solution was heated at 80 ° C for 10 hours. After the reaction was completed, the solution was cooled to room temperature. After adding 60 mL of chloroform, a white precipitate was obtained, which was then washed with a large amount of acetone. Finally, it was dried in a vacuum oven at 80 ° C. Maleic acid-α-cyclodextrin ester was obtained.
[0115] Preparation Example 2
[0116] Preparation of maleic acid-β-cyclodextrin ester: 11g of β-cyclodextrin, 10g of maleic anhydride and 10mL of N,N-dimethylformamide were stirred and mixed, and the mixture solution was heated at 80°C for 10 hours. After the reaction was completed, the solution was cooled to room temperature. A white precipitate was obtained after adding 60mL of chloroform, which was then washed with a large amount of acetone. Finally, it was dried in a vacuum oven at 80°C. Maleic acid-β-cyclodextrin ester was obtained.
[0117] Preparation Example 3
[0118] Preparation of maleic acid-γ-cyclodextrin ester: 12g of γ-cyclodextrin, 11g of maleic anhydride and 11mL of N,N-dimethylformamide were stirred and mixed, and the mixture solution was heated at 80°C for 10 hours. After the reaction was completed, the solution was cooled to room temperature. A white precipitate was obtained after adding 60mL of chloroform, which was then washed with a large amount of acetone. Finally, it was dried in a vacuum oven at 80°C. Maleic acid-γ-cyclodextrin ester was obtained.
[0119] Preparation Example 4
[0120] Preparation of maleic acid-2-hydroxypropyl-β-cyclodextrin ester: 14g of 2-hydroxypropyl-propyl cyclodextrin, 13g of maleic anhydride and 15mL of N,N-dimethylformamide were stirred and mixed, and the mixture solution was heated at 80°C for 10 hours. After the reaction was completed, the solution was cooled to room temperature. A white precipitate was obtained after adding 60mL of chloroform, which was then washed with a large amount of acetone. Finally, it was dried in a vacuum oven at 80°C. Maleic acid-2-hydroxypropyl-β-cyclodextrin ester was obtained.
[0121] Preparation Example 5
[0122] Preparation of maleic acid-2-hydroxypropyl-γ-cyclodextrin ester: 16g of 2-hydroxypropyl-propyl cyclodextrin, 15g of maleic anhydride and 18mL of N,N-dimethylformamide were stirred and mixed, and the mixture solution was heated at 80°C for 10 hours. After the reaction was completed, the solution was cooled to room temperature. A white precipitate was obtained after adding 60mL of chloroform, which was then washed with a large amount of acetone. Finally, it was dried in a vacuum oven at 80°C. Maleic acid-2-hydroxypropyl-γ-cyclodextrin ester was obtained.
[0123] Example 1
[0124] 0.54g of N-vinylpyrrolidone, 0.16g of allyltrimethylammonium chloride, 5.3g of 2-acrylamide-2-methylpropanesulfonic acid and 3g of maleic acid-β-cyclodextrin ester were mixed and dissolved with 41g of deionized water, nitrogen was introduced, and then the pH value of the system was adjusted to 6 with NaOH solution, 0.04g of initiator composition A (ammonium persulfate and sodium bisulfite) was added, and the reaction was carried out at 10°C for 7 hours. The system was cooled to room temperature, precipitated with acetone, filtered, dried, and crushed to obtain a polymer. The polymer test results are shown in Table 1.
[0125] The prepared polymer comprises:
[0126] Structural unit A( Among them, R 1 for R 4 is H);
[0127] Structural unit B( Formula (2-1) and The combination of formula (2-2), wherein R 5 is H, X is chloride ion);
[0128] Structural unit C( Wherein, Z is the residue after dehydroxylation of β-cyclodextrin);
[0129] Based on the total mass of the polymer, the content of the structural unit A is 58.9wt%, the content of the structural unit B is 7.8wt% (formula (2-1) is 6wt%, formula (2-2) is 1.8wt%, and the weight ratio is 3.3:1), and the content of the structural unit C is 33.3wt%.
[0130] Example 2
[0131] 5.3 g of 2-acrylamide-2-methylpropanesulfonic acid, 0.7 g of allyltrimethylammonium chloride and 3 g of maleic acid-β-cyclodextrin ester were mixed and dissolved with 41 g of deionized water, nitrogen was introduced, and then the pH value of the system was adjusted to 6 with NaOH solution, 0.04 g of initiator composition A (ammonium persulfate and sodium bisulfite) was added, and the reaction was carried out at 10° C. for 7 hours. The system was cooled to room temperature, precipitated with acetone, filtered, dried, and crushed to obtain a polymer. The polymer test results are shown in Table 1.
[0132] The prepared polymer comprises:
[0133] Structural unit A( Among them, R 1 for R 4 is H);
[0134] Structural unit B( Among them, R 5 is H, X is chloride ion);
[0135] Structural unit C( Wherein, Z is the residue after dehydroxylation of β-cyclodextrin);
[0136] Based on the total weight of the polymer, the content of the structural unit A is 58.9 wt %, the content of the structural unit B is 7.8 wt %, and the content of the structural unit C is 33.3 wt %.
[0137] Example 3
[0138] 5.3 g of 2-acrylamide-2-methylpropanesulfonic acid, 0.7 g of N-vinylpyrrolidone and 3 g of maleic acid-β-cyclodextrin ester were mixed and dissolved with 41 g of deionized water, nitrogen was introduced, and then the pH value of the system was adjusted to 6 with NaOH solution, 0.04 g of initiator composition A (ammonium persulfate and sodium bisulfite) was added, and the reaction was carried out at 10° C. for 7 hours. The system was cooled to room temperature, precipitated with acetone, filtered, dried, and crushed to obtain a polymer. The polymer test results are shown in Table 1.
[0139] The prepared polymer comprises:
[0140] Structural unit A( Among them, R 1 for R 4 is H);
[0141] Structural unit B( Among them, R 5 is H);
[0142] Structural unit C( Wherein, Z is the residue after dehydroxylation of β-cyclodextrin);
[0143] Based on the total weight of the polymer, the content of the structural unit A is 58.9 wt %, the content of the structural unit B is 7.8 wt %, and the content of the structural unit C is 33.3 wt %.
[0144] Example 4
[0145] 1.4 g of N-vinyl pyrrolidone, 3.6 g of acrylamide and 2.5 g of maleic acid-α-cyclodextrin ester were mixed and dissolved with 42.5 g of deionized water, nitrogen was introduced, and then the pH value of the system was adjusted to 6 with a NaOH solution, and 0.03 g of initiator composition A (ammonium persulfate and sodium bisulfite) was added, and the reaction was carried out at 10° C. for 6 hours. The system was cooled to room temperature, precipitated with acetone, filtered, dried, and crushed to obtain a polymer. The polymer test results are shown in Table 1.
[0146] The prepared polymer comprises:
[0147] Structural unit A( Among them, R 1 and R 4 All are H);
[0148] Structural unit B( Among them, R 5 is H, Y is );
[0149] Structural unit C( Wherein, Z is the residue after dehydroxylation of α-cyclodextrin);
[0150] Based on the total weight of the polymer, the content of the structural unit A is 48 wt %, the content of the structural unit B is 18.7 wt %, and the content of the structural unit C is 33.3 wt %.
[0151] Example 5
[0152] 2.6g of acryloyloxyethyl trimethylammonium chloride, 4.9g of N-dodecyl acrylamide and 2.5g of maleic acid-γ-cyclodextrin ester were mixed and dissolved with 40g of deionized water, nitrogen was introduced, and then the pH value of the system was adjusted to 8 with NaOH solution, 0.03g of initiator composition B (potassium persulfate and sodium bisulfite) was added, and the reaction was carried out at 40°C for 8 hours. The system was cooled to room temperature, precipitated with acetone, filtered, dried, and crushed to obtain a polymer. The polymer test results are shown in Table 1.
[0153] The prepared polymer comprises:
[0154] Structural unit A( Among them, R 1 C 12 The alkyl group, R 4 is H);
[0155] Structural unit B( Among them, R 5 is H, Y is
[0156] Structural unit C( Wherein, Z is the residue after dehydroxylation of γ-cyclodextrin);
[0157] Based on the total weight of the polymer, the content of the structural unit A is 49 wt %, the content of the structural unit B is 26 wt %, and the content of the structural unit C is 25 wt %.
[0158] Example 6
[0159] 3.1g of methacryloyloxyethyl dimethylbenzyl ammonium chloride, 5.9g of N-isopropylacrylamide and 2g of maleic acid-2-hydroxypropyl-β-cyclodextrin ester were mixed and dissolved with 39g of deionized water, nitrogen was introduced, and then the pH value of the system was adjusted to 8 with NaOH solution, followed by adding 0.05g of initiator composition B (potassium persulfate and sodium bisulfite), and reacted at 45°C for 8 hours. The system was cooled to room temperature, precipitated with acetone, filtered, dried, and crushed to obtain a polymer, and the polymer test results are shown in Table 1.
[0160] The prepared polymer comprises:
[0161] Structural unit A( Among them, R1 is isopropyl, R 4 is H);
[0162] Structural unit B( Among them, R 5 is H, Y is
[0163] Structural unit C( Wherein, Z is the residue after dehydroxylation of 2-hydroxypropyl-β-cyclodextrin);
[0164] Based on the total weight of the polymer, the content of the structural unit A is 53.6 wt %, the content of the structural unit B is 28.2 wt %, and the content of the structural unit C is 18.2 wt %.
[0165] Example 7
[0166] 2.2g (3-acrylamidopropyl) trimethylammonium chloride, 7.8g N-hydroxypropyl acrylamide and 2.5g maleic acid-2-hydroxypropyl-γ-cyclodextrin ester were mixed and dissolved with 37.5g deionized water, nitrogen was introduced, and then the pH value of the system was adjusted to 8 with NaOH solution, followed by adding 0.05g initiator composition B (potassium persulfate and sodium bisulfite), and reacted at 40°C for 9 hours. The system was cooled to room temperature, precipitated with acetone, filtered, dried, and crushed to obtain a polymer. The polymer test results are shown in Table 1.
[0167] The prepared polymer comprises:
[0168] Structural unit A( Among them, R 1 is hydroxyl group, R 4 is H);
[0169] Structural unit B( Among them, R 5 is H, Y is
[0170] Structural unit C( Wherein, Z is the residue after dehydroxylation of 2-hydroxypropyl-γ-cyclodextrin);
[0171] Based on the total weight of the polymer, the content of the structural unit A is 62.4 wt %, the content of the structural unit B is 17.6 wt %, and the content of the structural unit C is 20 wt %.
[0172] Example 8
[0173] 0.4g N-vinylpyrrolidone, 0.2g allyltrimethylammonium chloride, 4.4g 2-acrylamide-2-methylpropanesulfonic acid and 5g maleic acid-β-cyclodextrin ester were mixed and dissolved with 40g deionized water, nitrogen was introduced, and then the pH value of the system was adjusted to 6 with NaOH solution, 0.04g initiator composition A (ammonium persulfate and sodium bisulfite) was added, and the reaction was carried out at 10°C for 7 hours. The system was cooled to room temperature, precipitated with acetone, filtered, dried, and crushed to obtain a polymer. The polymer test results are shown in Table 1.
[0174] The prepared polymer comprises:
[0175] Structural unit A( Among them, R 1 for R 4 is H);
[0176] Structural unit B( Formula (2-1) and The combination of formula (2-2), wherein R 5 is H, X is chloride ion);
[0177] Structural unit C( Wherein, Z is the residue after dehydroxylation of β-cyclodextrin);
[0178] Based on the total mass of the polymer, the content of the structural unit A is 44wt%, the content of the structural unit B is 6wt% (formula (2-1) is 4wt%, formula (2-2) is 2wt%, and the weight ratio is 2:1), and the content of the structural unit C is 50wt%.
[0179] Example 9
[0180] 0.6g N-vinylpyrrolidone, 0.1g allyltrimethylammonium chloride, 5.3g 2-acrylamide-2-methylpropanesulfonic acid and 3g maleic acid-β-cyclodextrin ester were mixed and dissolved with 41g deionized water, nitrogen was introduced, and then the pH value of the system was adjusted to 6 with NaOH solution, 0.04g initiator composition A (ammonium persulfate and sodium bisulfite) was added, and the reaction was carried out at 10°C for 7 hours. The system was cooled to room temperature, precipitated with acetone, filtered, dried, and crushed to obtain a polymer. The polymer test results are shown in Table 1.
[0181] The prepared polymer comprises:
[0182] Structural unit A( Among them, R 1 for R 4 is H);
[0183] Structural unit B( Formula (2-1) and The combination of formula (2-2), wherein R 5 is H, X is chloride ion);
[0184] Structural unit C( Wherein, Z is the residue after dehydroxylation of β-cyclodextrin);
[0185] Based on the total mass of the polymer, the content of the structural unit A is 58.9wt%, the content of the structural unit B is 7.8wt% (formula (2-1) is 6.7wt%, formula (2-2) is 1.1wt%, and the weight ratio is 6.1:1), and the content of the structural unit C is 33.3wt%.
[0186] Comparative Example 1
[0187] 6g of 2-acrylamide-2-methylpropanesulfonic acid and 3g of maleic acid-cyclodextrin ester were mixed and dissolved with 41g of deionized water, nitrogen was introduced, and then the pH value of the system was adjusted to 6 with NaOH solution, 0.04g of initiator composition A (ammonium persulfate and sodium bisulfite) was added, and the reaction was carried out at 10°C for 7 hours. The system was cooled to room temperature, precipitated with acetone, filtered, dried, and crushed to obtain a polymer. The polymer test results are shown in Table 1.
[0188] Structural unit A( Among them, R 1 for R 4 is H);
[0189] Structural unit C( Wherein, Z is the residue after dehydroxylation of β-cyclodextrin);
[0190] Based on the total weight of the polymer, the content of the structural unit A is 66.7 wt %, and the content of the structural unit C is 33.3 wt %.
[0191] Comparative Example 2
[0192] 8.3 g of 2-acrylamide-2-methylpropanesulfonic acid, 0.54 g of N-vinylpyrrolidone and 0.16 g of allyltrimethylammonium chloride were mixed and dissolved with 41 g of deionized water, nitrogen was introduced, and then the pH value of the system was adjusted to 6 with a NaOH solution, and 0.04 g of initiator composition A (ammonium persulfate and sodium bisulfite) was added, and the reaction was carried out at 10° C. for 7 hours. The system was cooled to room temperature, precipitated with acetone, filtered, dried, and crushed to obtain a polymer. The polymer test results are shown in Table 1.
[0193] Structural unit A( Among them, R 1 for R 4 is H);
[0194] Structural unit B( B-1 and B-2 combination, in which R 5 ' is H, X is chloride ion);
[0195] Based on the total mass of the polymer, the content of the structural unit A is 92.2 wt%, and the content of the structural unit B is 7.8 wt% (Formula (2-1) is 6 wt%, Formula (2-2) is 1.8 wt%, and the weight ratio is 3.3:1).
[0196] Table 1
[0197]
[0198]
[0199] Test Example 1
[0200] The salt resistance of the polymers of Examples 1-9 and Comparative Examples 1-2 was evaluated. The results are shown in Table 2.
[0201] Table 2
[0202]
[0203] Test Example 2
[0204] The heat resistance of the polymers of Examples 1-9 and Comparative Examples 1-2 was evaluated, and the results are shown in Table 3.
[0205] Table 3
[0206]
[0207] Test Example 3
[0208] The anti-adsorption properties of the polymers of Examples 1-9 and Comparative Examples 1-2 were evaluated, and the results are shown in Table 4.
[0209] Table 4
[0210] <![CDATA[η 0 / cP]]> <![CDATA[η 1 / cP]]> Static adsorption viscosity retention rate / % Example 1 14.8 13.2 89 Example 2 13.9 12.2 88 Example 3 13.5 11.7 87 Example 4 12.4 10.7 86 Example 5 12. 10.3 86 Example 6 11.6 9.9 85 Example 7 11 9.4 85 Example 8 14.4 12.4 86 Example 9 14.7 12.8 87 Comparative Example 1 7.5 4.8 64 Comparative Example 2 5.9 3 51
[0211] The results show that the polymer of the present invention contains the structural unit A shown in formula (1), the structural unit B shown in formula (2) and the structural unit C shown in formula (3), and the obtained polymer has the following characteristics: (1) temperature resistance, the viscosity retention rate of the polymer at 85°C is ≥90%; (2) excellent salt resistance, at a mineralization degree of 100000 mg / L, the viscosity retention rate of the polymer is ≥80%; (3) excellent anti-adsorption performance, the static adsorption viscosity retention rate of the polymer is ≥85%. Furthermore, when the structural unit B of the present invention contains the specific structure shown in formula (2-1) and the structure shown in formula (2-2), a synergistic effect can be produced to further improve the heat resistance, salt resistance and anti-adsorption properties of the polymer.
[0212] Test Example 4
[0213] The polymers of Examples 1-9 and Comparative Examples 1-2 were respectively prepared with clean water to obtain a polymer aqueous solution with a mass concentration of 0.01 wt %. 0.1 parts by weight of sodium dodecyl sulfate was added to 100 parts by weight of clean water to prepare a displacement agent. The oil removal rates were tested respectively. The results are shown in Table 5.
[0214] Test Example 5
[0215] The polymers of Examples 1-9 and Comparative Examples 1-2 were mixed with water to prepare 2.5 wt % aqueous solutions, i.e., oil stain detergents. The oil stain cleaning rates were tested, and the test results are shown in Figure 5.
[0216] Table 5
[0217] Oil removal rate / vol% Oil cleaning rate / wt% Example 1 98 87 Example 2 97 85 Example 3 96 84 Example 4 94 83 Example 5 92 82 Example 6 91 82 Example 7 90 81 Example 8 95 82 Example 9 97 86 Comparative Example 1 76 67 Comparative Example 2 41 55
[0218] As can be seen from Table 5, compared with Comparative Examples 1-2, the displacement agent made of the polymer of the present invention has a more excellent oil displacement effect, and its static oil removal rate is ≥90%; further, when the preferred method is adopted, the displacement effect of the displacement agent of the present invention is better. In the oil-staining detergent made of the polymer of the present invention, since the cyclodextrin structure with internal hydrophilicity and external hydrophobicity is introduced into the polymer, it has the properties of a surfactant, so it can play a washing role without phase separation, and the oil-staining cleaning rate reaches more than 80%; when according to the preferred embodiment of the present invention, the washing performance of the oil-staining detergent is stronger.
[0219] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A polymer, characterized in that The polymer comprises at least one structural unit A represented by formula (1), at least one structural unit B represented by formula (2) and at least one structural unit C represented by formula (3), wherein: Where R1 is H, C1-C 18 Alkyl, -R2-SO3H, -R3-COOH or Wherein, R2 is a C3-C4 straight chain or branched alkyl group, R3 is a C4-C8 straight chain or branched alkyl group, n is an integer of 0-2, R4 is H or a C1-C4 straight chain alkyl group, and R5 is H or methyl; Y is selected from the structure shown in Formula I, the structure shown in Formula II, the structure shown in Formula III or the structure shown in Formula IV, wherein a is an integer of 0-22, b is 2, c is 1, d is 2 or 3, R6 is -COO- or -CO-NH-, and X is each independently a halogen; Z is the residue after dehydroxylation of cyclodextrin.
2. The polymer according to claim 1, wherein R1 is H, C3-C 12 Alkyl, -R2-SO3H, -R3-COOH or Wherein, R2 is isobutyl; R3 is isobutyl, n is 0 or 1, R4 is H or C1-C2 alkyl, and R5 is H; Preferably, a is an integer of 0-18, b is 2, c is 1, d is 2 or 3, R6 is -COO- or -CO-NH-, and X is a chloride ion; Preferably, the cyclodextrin is at least one selected from α-cyclodextrin, β-cyclodextrin, γ-cyclodextrin, 2-hydroxypropyl-β-cyclodextrin and 2-hydroxypropyl-γ-cyclodextrin.
3. The polymer according to claim 1 or 2, wherein Based on the total mass of the polymer, the content of the structural unit A is 40-65wt%, preferably 45-63wt%; The content of the structural unit B is 5-30 wt%, preferably 7-29 wt%; the content of the structural unit C is 15-40 wt%, preferably 18-35 wt%.
4. The polymer according to any one of claims 1 to 3, wherein The structural unit B includes the structure shown in formula (2-1) and the structure shown in formula (2-2); Preferably, in the structural unit B, the weight ratio of the structure represented by the formula (2-1) to the structure represented by the formula (2-2) is 1-4:
1.
5. The polymer according to any one of claims 1 to 4, wherein The viscosity-average relative molecular weight of the polymer is 1,000,000-8,000,000 g / mol, preferably 1,000,000-6,000,000 g / mol.
6. A method for preparing a polymer, characterized in that: The method comprises: mixing at least one monomer A represented by formula (4), at least one monomer B represented by formula (5) and at least one monomer C represented by formula (6) with water to obtain a monomer mixed solution, adjusting the pH value of the monomer mixed solution, adding an initiator, performing a polymerization reaction under a nitrogen atmosphere, and obtaining a polymer through post-treatment; Wherein, R1' is H, C1-C 18 Alkyl, -R2'-SO3H, -R3'-COOH or wherein R2' is a C3-C4 straight chain or branched alkyl group, R3' is a C4-C8 straight chain or branched alkyl group, n' is an integer of 0-2, R4' is H or a C1-C4 straight chain alkyl group, and R5' is H or methyl; Y' is selected from the structure shown in formula I', the structure shown in formula II', the structure shown in formula III' or the structure shown in formula IV', wherein a' is an integer of 0-22, b' is 2, c' is 1, d' is 2 or 3, R6' is -COO- or -CO-NH-, and X' is each independently a halogen; Z' is the residue after dehydroxylation of cyclodextrin.
7. The preparation method according to claim 6, wherein: R1' is H, C3-C 12 Alkyl, -R2'-SO3H, -R3'-COOH or Wherein, R2' is isobutyl; R3' is isobutyl, n' is 0 or 1, R4' is H or C1-C2 alkyl, and R5' is H; Preferably, a' is an integer of 0-18, b' is 2, c' is 1, d' is 2 or 3, R6' is -COO- or -CO-NH-, and X' is a chloride ion; Preferably, the cyclodextrin is at least one selected from α-cyclodextrin, β-cyclodextrin, γ-cyclodextrin, 2-hydroxypropyl-β-cyclodextrin and 2-hydroxypropyl-γ-cyclodextrin.
8. The preparation method according to claim 6 or 7, wherein: Based on the total mass of the monomer A, monomer B and monomer C, the amount of the monomer A is 40-65wt%, preferably 45-63wt%; the amount of the monomer B is 5-30wt%, preferably 7-29wt%; the amount of the monomer C is 15-40wt%, preferably 18-35wt%.
9. The preparation method according to any one of claims 6 to 8, wherein: The monomer B includes the structure shown in formula (5-1) and the structure shown in formula (5-2); Preferably, relative to the total amount of monomer B used, the amount ratio of monomer B having the structure represented by formula (5-1) to monomer B having the structure represented by formula (5-2) is 1-4:
1.
10. The preparation method according to any one of claims 6 to 9, wherein: The initiator is selected from at least one of sodium bisulfite, sodium thiosulfate, sodium pyrosulfite, potassium persulfate, sodium persulfate, hydrogen peroxide, 2,2'-azo[2-(2-imidazolin-2-yl)propane] dihydrochloride, azobis(2,5-dimethyl-6-carboxyl)hexanenitrile and 4,4'-azobis(4-cyanovaleric acid), preferably an initiator composition of potassium persulfate and sodium bisulfite, or an initiator composition of ammonium persulfate and sodium bisulfite; Preferably, based on the total weight of the monomer A, the monomer B and the monomer C, the added amount of the initiator is 0.1-0.6 wt %, preferably 0.3-0.6 wt %.
11. The preparation method according to any one of claims 6 to 10, wherein: Adjust the pH value of the monomer mixed solution to 6-8; Preferably, the polymerization reaction temperature is 5-50°C, preferably 10-40°C; the polymerization reaction time is 6-9h, preferably 7-8h.
12. A polymer obtained by the preparation method according to any one of claims 6 to 11; Preferably, the viscosity-average relative molecular weight of the polymer is 1,000,000-8,000,000 g / mol, preferably 1,000,000-6,000,000 g / mol.
13. Use of the polymer according to any one of claims 1 to 5 and 12 as a displacement agent.
14. Use of the polymer according to any one of claims 1 to 5 and 12 as an oily dirt detergent.
15. A displacement agent, characterized in that: The displacement agent comprises the polymer according to any one of claims 1 to 5 and 12 and water; Preferably, relative to 100 parts by weight of water, the polymer is 0.1-5 parts by weight, preferably 0.1-2.5 parts by weight; Preferably, the displacement agent further comprises a surfactant.
Citation Information
Patent Citations
Method for preparing AA / AM / MAH-beta-CD ternary oil-displacing agent
CN104877078A
Ultrahigh-temperature salt-tolerant star polymer filtrate reducer, preparation method thereof and water-based drilling fluid
CN111909670A
Anti-shearing modified polyacrylamide and application thereof
CN114262412A
Copolymers and their use in detergent compositions
US20200063070A1
